The long dumb road [videorecording (DVD)] - Revolori, Tony, 1996-; Delao, David; Martinez-Cunningham, Lora (Universal Pictures Home Entertainment, 2019)
Two guys meet by chance during a period of each of their lives when they are at a crossroads, and they decide to go on a trip across the southwest part of America.